2022
DOI: 10.2217/fvl-2021-0066
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lopinavir–Ritonavir Combination Therapy for the Treatment of Hospitalized COVID-19 Patients: A Meta-Analysis

Abstract: Aim: To evaluate the efficacy and safety of lopinavir–ritonavir (LPV/r) therapy in treating hospitalized COVID-19 patients. Materials & methods: Data from randomized and observational studies were included in meta-analyses. Primary outcomes were length of stay, time for SARS-CoV-2 test conversion, mortality, incidence of mechanical ventilation, time to body temperature normalization and incidence of adverse events. Results: Twenty-four studies (n = 10,718) were included. LPV/r demonstrated no significant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 116 publications
0
8
0
1
Order By: Relevance
“…Specifically, the efficacy and safety of several antiviral therapies, as well as immunomodulatory regimens, have been thoroughly investigated and described in the literature. However, many of the antiviral therapies, such as chloroquine, lopinavir–ritonavir, and ivermectin, have been consistently shown in randomized controlled trials (RCTs) and meta-analyses to confer little to no clinical efficacy against SARS-CoV-2 [ 1 3 ]. Meanwhile, immunomodulatory agents such as dexamethasone were found to only be effective among patients with severe disease receiving respiratory support, with little to no efficacy in patients with mild symptoms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the efficacy and safety of several antiviral therapies, as well as immunomodulatory regimens, have been thoroughly investigated and described in the literature. However, many of the antiviral therapies, such as chloroquine, lopinavir–ritonavir, and ivermectin, have been consistently shown in randomized controlled trials (RCTs) and meta-analyses to confer little to no clinical efficacy against SARS-CoV-2 [ 1 3 ]. Meanwhile, immunomodulatory agents such as dexamethasone were found to only be effective among patients with severe disease receiving respiratory support, with little to no efficacy in patients with mild symptoms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Wen et al (2020) [ 38 ] demonstrated that LPV/r did not promote virus negative conversion and clinical improvement in COVID-19 patients [ 39 ]. An updated systematic review examined whether the use of LPV/r could be more favorable compared to the standard therapies regarding the length of stay, time for positive-to-negative conversion of SARS-CoV-2 and mortality in hospitalized patients with COVID-19, concluding that LPV/r had no significant advantage and also registered a significant increase in the occurrence of side effects [ 40 ]. However, Elmekaty et al [ 41 ] showed that early treatment with LPV/r is associated with a faster clinical improvement and/or virological clearance than the darunavir/cobicistat therapy in patients with COVID-19 pneumonia, and that the safety profile was quite comparable.…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…В наиболее раннем метаанализе исследований за период до мая 2020 г. при сравнении 7 перепрофилированных препаратов для лечения COVID-19 (рибавирин, хлорохин, гидроксихлорохин, умифеновир, фавипиравир, интерферон и лопинавир/ритонавир) показано, что только лопинавир/ ритонавир вызывал наиболее достоверные побочные эффекты со стороны ЖКТ в виде усиления диареи, тошноты и рвоты [46]. В последующих двух метаанализах 2020 и 2022 г. проводилась оценка безопасности непосредственно лопинавира/ ритонавира при лечении госпитализированных пациентов с COVID-19, и основные побочные эффекты также отмечены со стороны ЖКТ -диарея, тошнота, рвота, боль в животе, потеря аппетита и гепатотоксичность в виде повышения уровня печеночных трансаминаз и билирубина [47,48]; ОР неблагоприятных эффектов составил 2,88 (ДИ 1,04-7,95; р<0,01) [48].…”
Section: лопинавир/ритонавирunclassified